Public pensions and intra-EU mobility: An unfinished agenda - Jakob von Weizsäcker; Robert Fenge (Bruegel, 2008)
We distinguish two ways in which national public pension systems can distort intra-EU movements of workers. First, each national pension system may display an inherent mobility bias. We propose the 'Lodge Test' to identify any such bias and show that many national pension systems in the EU are not mobility neutral. Second, mobility distortions may arise from differences between national pension systems. Using the CESifo pension model, we estimate both average and year-by-year implicit tax rates for select national pension systems in the EU. We then discuss how the observed differences in implicit tax rates on income may distort mobility and might even give rise to age-specific tax competition.
Keywords: 330